Antigua and Barbuda. Significant achievements 2020 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (2021)
The main activities carried out by the Institute in Antigua and Barbuda during 2020 are identified, with respect to the needs and interests of the country, identifying problems in adaptive technologies for family farming, climate change, food security and technological innovation. Likewise, among the achievements carried out, the progress of the different projects implemented, the extension activities in the dissemination of information with publications, forums, training and research are recognized. Finally for the recovery of the rural sector due to the post-COVID-19, it provided agricultural inputs and supplies to help boost the production of small farmers and coordinated virtual meetings to address the negative impact of the COVID-19 pandemic and the protocols and solutions that should be implemented to support the Institute's technical cooperation model.